1970
DOI: 10.1159/000192697
|View full text |Cite
|
Sign up to set email alerts
|

The Nasal Respiratory Handicap of Expiratory Airflow Disease: The Response to Bronchodilator Aerosols

Abstract: Fifty normal adults and 50 patients with chronic bronchitis and diffuse obstructive pulmonary emphysema, all free of nasal impediments, had lower airways and nasal resistances determined by plethysmographic subtraction; Rn was also determined by electronic posterior rhinometry. Twenty of the patients pursued a double-blind crossover trial in which isoproterenol, phenylephrine, isoproterenol-phenylephrine, and placebo were given as one dose on four consecutive days from identical hand nebulizers by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1972
1972
1987
1987

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Hiley, Wilson & Yates (1978) reported that /J2-adrenoceptors were present in the feline capacitance vessels. In man, topical administration of isoprenaline or terbutaline results in either a variable response (McLean, Mathews, Ciarkowski, Brayton & Solomon, 1976), an increase in airway pressure (Grobler, 1966) or no effect (Cohen, 1970;Svensson, Hegardt & Lofkvist, 1980). Our results suggest that ,,-and fl2-adrenoceptors are present in the nose of the dog.…”
Section: Nasal Airway Resistancementioning
confidence: 62%
“…Hiley, Wilson & Yates (1978) reported that /J2-adrenoceptors were present in the feline capacitance vessels. In man, topical administration of isoprenaline or terbutaline results in either a variable response (McLean, Mathews, Ciarkowski, Brayton & Solomon, 1976), an increase in airway pressure (Grobler, 1966) or no effect (Cohen, 1970;Svensson, Hegardt & Lofkvist, 1980). Our results suggest that ,,-and fl2-adrenoceptors are present in the nose of the dog.…”
Section: Nasal Airway Resistancementioning
confidence: 62%
“…These differences were not unexpected in view of the central location of the subepithelial receptors responsible for cough and for reflex bronchoconstriction [38], The same determinations (R", [R" + R J, and Cl) appeared most useful in reflect ing meaningful differences among the various treatment formulations, among a single formulation and its components, and between active drug mixtures and a matched placebo. The trends of total and lower airway re- sistance changes again suggest that consideration of nasal and lower tract flow resistances, obtained in concert, is more helpful and precise than re liance upon R;i-based indices alone in defining the site and total activity of respiratory medications, implementing our earlier conclusions from aerosol trials [39,40],…”
Section: Discussionmentioning
confidence: 66%
“…Grobler [10] and McLean et al [18] observed a swelling of the nasal mucosa after isoproterenol spraying, but this was de nied by Cohen [9]. Borum and Mygind [6] and Schumacker [21] detected a slight but statistically significant swelling of the nasal mucosa when it was sprayed with fenoterol, a Pj-receptor agonist.…”
Section: Discussionmentioning
confidence: 99%